Evaluation of the diagnostic accuracy of microalbuminuria in predicting mortality among elderly patients with sepsis - Bar, Mita; Mukhopadhyay, Prianka; Biswas, Atanu; Sarkar, Manisha (Asian Journal of Medical Sciences, 2023)
Background: Sepsis is a common cause of morbidity and mortality among geriatrics. Aims and Objectives: The objective of study was to find the clinicomicrobiological profile of elderly inpatients (≥60 years) with sepsis and to evaluate the diagnostic accuracy of urine albumin to creatinine ratio (ACR) or microalbuminuria in predicting mortality. Materials and Methods: A prospective observational study was conducted among 50 geriatric patients admitted with sepsis in the ward or intensive therapy unit under medicine department of a tertiary care center for a period of 1 year. Baseline clinicomicrobiological profile was noted. Urine ACR values were measured at admission, day 4, and day 7 and geriatrics were followed up for 28 days to see the outcome. Receiver operator characteristic curve analysis was performed to evaluate the area under the curve for microalbuminuria on the 3 days and to determine the optimum cut-off points to predict mortality. Results: The mortality rate within 28 days was 64%. Urine microalbuminuria on day 1, day 4, and day 7 of admission was significantly higher among the non-survivors compared to survivors (P≤0.001, P≤0.001, and P=0.006, respectively). Microalbuminuria levels (in mcg/mg) of 143.0, 60.05, and 42.6 on day 1, 4, and 7 of admission, respectively, can be used as the cut-off to predict the death of geriatric sepsis inpatients with overall diagnostic accuracy of 83.0%, 83.4% and 86.1%, respectively, sensitivity as 93.75%, 87.50%, and 100.0%, respectively, and specificity as 44.44%, 72.22%, and 72.22%, respectively. Conclusion: Microalbuminuria can be a potential biomarker to predict death among geriatric septic inpatients, which can further help in improving the treatment strategy.